PERAN GURU BIMBINGAN KONSELING DALAM MENGATASI PELANGGARAN MORAL DI MADRASAH ALIYAH NEGERI (MAN) KOTA BATU - Ihda Nailul Muna; Chalimatus Sadijah; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the role of counseling teachers in overcoming moral violations. The problem faced is the number of moral violations that occur among teenagers or students. Therefore, the role of counseling teachers is very necessary to overcome them. Data sources were obtained from counseling tutors, problem students, homeroom teachers from problem students, and deputy head of student affairs. This research uses interview, observation, and documentation methods. Then analyzed by data reduction, data presentation, and conclusion. The results of this study indicate that the role of counseling teachers is very important and counseling teacher carry out their strategies well in dealling with moral violations. Thus making student better at behaving, both at school and outside school.Keyword: teacher, counseling guidance, moral violation